Experimental Study on Seismic Behavior of Coupled Steel Plate and Reinforced Concrete Composite Wall - Zhenbang Ma; Yuntian Wu; Jie Zhang; Mao Zhang (Buildings, 2022)
The coupled steel plate and reinforced concrete (C-SPRC) composite wall is a new type of coupled-wall system consisting of steel coupling beams (SCBs) that join two SPRC walls where the steel plate shear wall (SPSW) is embedded in the RC wall. Although the C-SPRC wall has been extensively constructed in high-rise buildings in seismic regions, research on its behavior has rarely been reported. No code provisions are available for directly guiding the preliminary design of such coupled-wall systems. In the research, three 1/3-scaled C-SPRC wall subassemblies including one-and-a-half stories of SPRC walls and a half-span of SCB were tested under simulated earthquake action, considering the fabrication method of the embedded SPSW and the shear-span ratio of the SPRC walls as two test variables. The prime concern of the research was to evaluate the influences of those popular design and construction parameters on the seismic behavior of the C-SPRC wall. Deviating from the beam tip loading method used in conventional subassembly tests, the lateral cyclic load in this research was applied at the top of the wall pier so that the behaviors of both walls and SCBs could be examined. The test results exhibited the great seismic performance of the subassemblies with the coupling mechanism fully developed. The energy dissipation capacity and inter-story deformation capacity of the subassembly with the assembled SPSW were roughly 9.4% and 13.2% greater than those with the conventional welded SPSW. Compared with the subassembly with the shear-span ratio of 2.2, the interstory-deformation capacity of the one with the shear-span ratio of 2.0 was increased by approximately 13.4%, while the energy dissipation capacity was decreased by 10.9%. The test results were further compared with the simulation results using the proven-reliable finite element analysis with respect to the hysteretic curves, skeleton curves, energy dissipation capacities and failure patterns.